2018
DOI: 10.1111/bcp.13814
|View full text |Cite
|
Sign up to set email alerts
|

Comparative safety and effectiveness of direct oral anticoagulants in patients with atrial fibrillation in clinical practice in Scotland

Abstract: AimsThe aim of this study was to compare the clinical effectiveness and safety of direct oral anticoagulants (DOACs) in patients with atrial fibrillation (AF) in routine clinical practice.MethodsThis retrospective cohort study used linked administrative data. The study population (n = 14 577) included patients with a diagnosis of AF (confirmed in hospital) who initiated DOAC treatment in Scotland between August 2011 and December 2015. Multivariate Cox proportional hazard models were used to estimate hazard rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 32 publications
9
61
0
Order By: Relevance
“…It has been reported that patients with chronic liver disease treated with DOACs have a lower incidence of major bleeding compared with VKAs [56,57]. Several DOACs rankings [58][59][60] and expert opinions have been published to assist physicians to fit the best DOAC according to individual patient's characteristics [61][62][63][64]. Apixaban has been suggested as a reasonable first choice either in older patients and in subjects with chronic renal failure [63].…”
Section: Selection and Dosing Of Doacmentioning
confidence: 99%
“…It has been reported that patients with chronic liver disease treated with DOACs have a lower incidence of major bleeding compared with VKAs [56,57]. Several DOACs rankings [58][59][60] and expert opinions have been published to assist physicians to fit the best DOAC according to individual patient's characteristics [61][62][63][64]. Apixaban has been suggested as a reasonable first choice either in older patients and in subjects with chronic renal failure [63].…”
Section: Selection and Dosing Of Doacmentioning
confidence: 99%
“…Regulation (EC) No 726/2004 allows joint regulatory and HTA scientific advice for applicant MAHs at an early stage of development of a medicinal product, and this experience is generally considered positively [81]. However, there is currently a lack of collaboration between medicines regulation and HTA, as well as pricing and reimbursement authorities, in monitoring the effectiveness of new medicines during the post-authorisation phase, although this is increasingly happening at a national level [52,72,[82][83][84][85][86]. With the introduction of conditional approvals, there is a shift in responsibility for effectiveness from the marketing authorisation to the post-authorisation phase [87], and this also brings added burden on the financing of new medicines by national healthcare systems.…”
Section: Consolidation Of Other Relevant Opinions and Recommendationsmentioning
confidence: 99%
“…These new models include encouraging the use of biosimilars and multiple sourced products where pertinent to conserve resources alongside instigating active disinvestment processes (Godman et al, 2014a;WHO, 2015;Parkinson et al, 2015;Guerra-Junior et al, 2017;Moorkens et al, 2017;Godman et al, 2018) as well as a growing use of managed entry agreements (MEAs). However, there are concerns with MEAs including the extent and usefulness of any clinical data collected, as well as the ability to actively monitor the role and value of new medicines in routine clinical care to provide future guidance (Ferrario and Kanavos, 2013;WHO, 2015;Garattini and Curto, 2016;Carlson et al, 2017;Ferrario et al, 2017;Garcia-Doval et al, 2017;Guerra-Junior et al, 2017;Mercer et al, 2017;Eriksson et al, 2018;Frisk et al, 2018;Alvarez-Madrazo et al, 2019;Antonanzas et al, 2019;Mueller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%